2018
DOI: 10.1002/bdr2.1374
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how the concentration of neighborhood advantage and disadvantage affects spina bifida risk among births to non‐Hispanic white and Hispanic women, Texas, 1999–2014

Abstract: Findings suggest spina bifida risk is associated with neighborhood disadvantage or advantage, and that relationship seems to vary by race-ethnicity. The varied associations between ICE measures and spina bifida by race/ethnicity highlights the importance of using targeted interventions in the prevention of spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Similar patterns were found in the separate analysis of Mexican births to foreign-born and US-born mothers for these conditions except for anotia/microtia (although elevated but not statistically significant). These findings are generally concordant with those reported by Shumate et al (2018), Padula et al (2017), and Hoyt et al (2014). Among infants born to non-Hispanic black women, prevalence was significantly lower for only one condition, pyloric stenosis, while higher prevalence was found for trisomy 13 and 18 among those with foreign-born mothers.…”
Section: | Discussionsupporting
confidence: 89%
“…Similar patterns were found in the separate analysis of Mexican births to foreign-born and US-born mothers for these conditions except for anotia/microtia (although elevated but not statistically significant). These findings are generally concordant with those reported by Shumate et al (2018), Padula et al (2017), and Hoyt et al (2014). Among infants born to non-Hispanic black women, prevalence was significantly lower for only one condition, pyloric stenosis, while higher prevalence was found for trisomy 13 and 18 among those with foreign-born mothers.…”
Section: | Discussionsupporting
confidence: 89%
“…Previous research has shown variation in prevalence of this gene among different racial/ethnic groups, in which a C to T mutation at nucleotide 677 is a risk factor for cardiovascular defects and NTDs (Franco, Araújo, Guerreiro, Elion, & Zago, ; Wilken et al, ). Additionally, sociodemographic factors such as nativity, individual socioeconomic status, and neighborhood were not further explored, but may also impact the prevalence of birth defects (Kirby et al, ; Shumate, Hoyt, Liu, Kleinert, & Canfield, ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this opens up avenues for other variations of the ICE that might incorporate explanatory factors other than income. In fact, several studies have already tested new ICE measures that account for spatial polarization of deprivation and privilege by housing tenure (owners vs. renters) [30], education (high vs. low) [71,72], as well as nativity (U.S. born vs. foreign) and PLOS ONE language (English vs. foreign language) [72]. While we find that ICE Race-Income accounts for a relatively large portion of the variance in the link between segregation and health, these new versions of the ICE may be useful in the effort to further disentangle this complex association and uncover additional underlying pathways.…”
Section: Practical and Methodological Implicationsmentioning
confidence: 99%